T-Pattern Detection in Judo Combat: An Approach to Training Male Judokas with Visual Impairments According to their Weight Category - Gutierrez-Santiago, A.; Prieto, I.; Ayan, C.; Cancela, J. (International Journal of Sports Science and Coaching, 2013)
This study aimed to describe the temporal structure of judo combat for the different weight categories in men with visual impairments so that coaches can adapt traditional judo training methods to this specific population. Observational methodology was used in 184 combats (n = 92 male senior judokas with visual impairments). A T-Patterns study (THEME) and a descriptive and inferential statistical analysis were carried out. The results showed that most of the observed combats ended before regulation time was over (81%). The different weight categories must be taken into account in order to establish adequate training patterns for this population. Special attention must be paid to Work Sequence Time in Stand-up Judo (WSSQT) since this parameter showed significant differences (p = 0.001). The mean values obtained in the studied combats indicate that visual disability accounts for the shorter work sequences and longer pause sequences observed in this group of judokas. These results confirmed that the temporal structure of judo combat in male athletes with visual impairments is different from that of fully-sighted ones. Given all that, a different approach to training each group of judokas becomes necessary, since the temporal structure of the combat is different in each case.